Chemical research should be a national priority - Uprety, Rajendra (Himalayan Journal of Sciences, 2006)
Though Nepal has been active in natural product screening, the total national research effort is negligible. Little of the research that is carried out is appropriate for the natural and social constraints. Natural resources are being overlooked, and data that is collected is not thoroughly analyzed and reported.Himalayan Journal of Sciences 2(3): 10, 2004The full text is of this article is available at the Himalayan Journal of Sciences website